HPV oral atypical lesion in Aids patient case report - Martinelli, Fabio Leoncio B.; Leite, Andréa G.B.; Miranda, Paula P.T. de; Barra, Luiz Alberto C.; Bedaque, Eleni Aparecida (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Human papillomavirus lesions are frcquently found as condylomas in the anogenital region. Unusual presentations may be found in severely immunosu- ppressed patients. In this report. an HIV patient with CDh- count: 0 cels/mm had a history of intermittent occurrence of oral lesions. dysphagia and weight loss in lhe last 8 months. Oropharynx examination showed a 3cm ulcera te d lesion. He was referred to Emilio Ribas Institute where specific treatment for cytomegaiovirus showed no response. Thalidomide administration also showed no response. Histological study of the lesion revealed koilocytosis thal was compatible with papillomavirus infection. Oral cavity warts in immunosuppressed patients can be duc to several conditions. As a worldwide sexually transmilted disease, this hypothesis should be considered in patients with aids and oral warts.